Procalcitonin algorithm to guide initial antibiotic therapy in acute exacerbations of COPD admitted to the ICU: a randomized multicenter study - Daubin, Cédric; Valette, Xavier; Thiollière, Fabrice; Mira, Jean-Paul; Hazera, Pascal; Annane, Djillali; Labbe, Vincent; Floccard, Bernard; Fournel, François; Terzi, Nicolas; Du Cheyron, Damien; Parienti, Jean-Jacques (Intensive care medicine, 2018)
Purpose To compare the efficacy of an antibiotic protocol guided by serum procalcitonin (PCT) with that of standard antibiotic therapy in severe acute exacerbations of COPD (AECOPDs) admitted to the intensive care unit (ICU). Methods We conducted a multicenter, randomized trial in France. Patients experiencing severe AECOPDs were assigned to groups whose antibiotic therapy was guided by (1) a 5-day PCT algorithm with predefined cutoff values for the initiation or stoppage of antibiotics (PCT group) or (2) standard guidelines (control group). The primary endpoint was 3-month mortality. The predefined noninferiority margin was 12%. Results A total of 302 patients were randomized into the PCT ( n = 151) and control ( n = 151) groups. Thirty patients (20%) in the PCT group and 21 patients (14%) in the control group died within 3 months of admission (adjusted difference, 6.6%; 90% CI − 0.3 to 13.5%). Among patients without antibiotic therapy at baseline ( n = 119), the use of PCT significantly increased 3-month mortality [19/61 (31%) vs. 7/58 (12%), p = 0.015]. The in-ICU and in-hospital antibiotic exposure durations, were similar between the PCT and control group (5.2 ± 6.5 days in the PCT group vs. 5.4 ± 4.4 days in the control group, p = 0.85 and 7.9 ± 8 days in the PCT group vs. 7.7 ± 5.7 days in the control group, p = 0.75, respectively). Conclusion The PCT group failed to demonstrate non-inferiority with respect to 3-month mortality and failed to reduce in-ICU and in-hospital antibiotic exposure in AECOPDs admitted to the ICU.